Can the world become a place where the planet and all people flourish after the pandemic?. (3rd May 2022) - Baum, Fran; Paremoer, Lauren; Flavel, Joanne; Musolino, Connie; Labonte, Ronald
Abstract : Covid-19 has impeded achievement of the sustainable development goals and a radical rethink of the global economy is required to meet them argue Fran Baum and colleagues